Two-part (meth)acrylate adhesive composition

CN122935585APending Publication Date: 2026-10-16HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580021053.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-14
Filing Date
2025-03-14
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0010] The compositions of the present invention work particularly quickly on C5-coated substrates, and also on non-C5-coated substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a two-part room temperature vulcanizable adhesive composition and its use. The adhesive composition has high tensile strength and fast set time and is particularly useful on low surface energy or non-active metal substrates such as C5 electrical steel, coated substrates. The composition comprises: a first part adhesive composition containing one or more (meth)acrylic hydroxyalkyl ester monomers, a polyfunctional polyurethane oligomer, and an adhesion promoter; and a second part primer composition containing a nitrogen containing compound, a copper based catalyst, and a diluent component. The primer composition comprises an amine activator, a copper based catalyst and one or more diluents comprising (meth)acrylic hydroxyalkyl ester monomers and a solvent; desirably present in specific percentage ratios to each other, the primer composition desirably miscible in hydrocarbon oils.
Need to check novelty before this filing date? Find Prior Art

Description

background Technical Field

[0001] This invention relates to a two-part room-temperature curable adhesive composition and its uses. The adhesive composition exhibits high tensile strength and rapid fixation time, and is particularly suitable for use on low surface energy or inactive metallic substrates, such as C5-coated steel. The adhesive composition comprises an adhesive portion and a primer portion, wherein the primer portion is desirablely, but not necessarily, miscible with hydrocarbon oils. Background Technology

[0002] Commercial applications across various industries, including welding and manufacturing, require the use of a wide range of metals, including steel. Various types of steel and steel coatings exist, including but not limited to, CS / EC-5 electrical steel, galvanized steel, low-carbon steel, and stainless steel. Some metals (such as CS / ES-5 electrical steel) can be considered low surface energy substrates, making them difficult to bond to surfaces. However, using CS / EC-5 electrical steel offers advantages due to its increased insulation properties, annealing resistance, and improved weldability. Therefore, the issue of insufficient adhesive properties needs to be addressed.

[0003] In industrial applications, the presence of a certain amount of cutting oil on metal substrates during the cutting process is common. The presence of cutting oil can hinder adhesion. Therefore, it is necessary to address the problem of insufficient adhesive properties in the presence of cutting oil.

[0004] In industrial applications, such as the high-efficiency electric motor industry, the use of various types of steel and other metals (including but not limited to CS / EC-5 electrical steel) in the manufacture / welding of laminated stacks is common. During the manufacturing process, materials move through the assembly line at each step of the process, typically at room temperature in a factory setting. Manufacturing lines often need to be able to handle and move parts quickly and efficiently. Therefore, parts bonded with adhesives require a fast settling time so that the parts can be moved and handled without damaging the adhesive.

[0005] Current methods for bonding laminated stacks include adhesive bonding, mechanical interlocking, and welding. Each of these methods has its advantages and disadvantages. Laminated stacks are typically formed using a pre-applied adhesive coating that is activated by pressure and temperature. However, these adhesives have limited shelf life and require the introduction of pressure and heat over time to activate the bond, making them less than ideal solutions. Mechanical interlocking does not provide an intermediate electrical insulation layer and does not provide a region of increased thermal conductivity for heat dissipation. Welding is a method in which all stacks are joined together and none of them are electrically insulating. All of these methods require additional steps. Current adhesive solutions include epoxy resins, which cure slowly and require additional heating steps.

[0006] Therefore, there is a need in industry for a highly efficient adhesive composition that can be applied to various metals (including low surface energy CS / EC-5 electrical steel) with a rapid curing / setting time at room temperature. There is also a need in industry for a composition that meets these requirements in the presence of cutting oil. Summary of the Invention

[0007] This invention solves the aforementioned problems by preparing a two-part composition comprising a novel adhesive and primer composition, which cures / fixes rapidly at room temperature and exhibits good adhesion to low surface energy CS / EC-5 electrical steel. In addition to its rapid setting time, the composition of this invention also possesses strong tensile shear strength when applied to CS / EC-5 electrical steel.

[0008] The new primer composition is also miscible / soluble in cutting oils that may be present during the stamping process.

[0009] The two-part composition can also have even faster room temperature curing / setting time and stronger adhesive strength when applied to substrates with non-low surface energy.

[0010] The compositions of the present invention work particularly quickly on C5-coated substrates, and also on non-C5-coated substrates.

[0011] An advantageous aspect of the present invention provides a two-part room-temperature curable composition comprising: a) A first-part adhesive composition comprising: i) One or more (meth)acrylate hydroxyalkyl ester monomers present in an amount of about 10% to about 45% by weight of the first part of the composition; ii) a multifunctional polyurethane (meth)acrylate oligomer present in an amount of about 10% to about 50% by weight of the first part of the composition; and iii) Adhesion accelerators; and b) The second part of the primer composition contains: i) A nitrogen-containing compound present in an amount of about 0.05% by weight to about 10% by weight of the second part of the composition; ii) a copper-based catalyst present in an amount of about 0.1% to about 15% by weight of the second part of the composition; and iii) Diluent components; The composition provides a room temperature fixation time of about 5 to about 35 seconds; and After curing at room temperature on a substrate for 24 hours, the composition exhibits a shear strength of approximately 2.5 MPa to approximately 10 MPa; and The substrate is a C5 coated substrate.

[0012] Another advantageous aspect of the invention provides a two-part room temperature curable composition comprising: a) A first-part adhesive composition comprising: i) One or more (meth)acrylate hydroxyalkyl ester monomers present in an amount of about 10% to about 45% by weight of the first part of the composition; ii) a multifunctional polyurethane (meth)acrylate oligomer present in an amount of about 10% to about 50% by weight of the first part of the composition; and iii) Adhesion accelerators; and b) The second part of the primer composition contains: i) A nitrogen-containing compound present in an amount of about 0.05% by weight to about 10% by weight of the second part of the composition; ii) a copper-based catalyst present in an amount of about 0.1% to about 15% by weight of the second part of the composition; and iii) Diluent components; The composition provides a room temperature fixation time of about 5 to about 35 seconds; and After curing at room temperature on a substrate for 24 hours, the composition exhibits a shear strength of approximately 3.0 MPa to approximately 10 MPa; and The substrate mentioned is not a C5 coated substrate.

[0013] Another advantageous aspect of the invention provides a rotor assembly for an electric motor, comprising two or more substrates joined together by an adhesive composition to form a laminated stack. The adhesive composition comprises: a) A first-part adhesive composition comprising: i) One or more (meth)acrylate hydroxyalkyl ester monomers present in an amount of about 10% to about 45% by weight of the first part of the composition; ii) a multifunctional polyurethane (meth)acrylate oligomer present in an amount of about 10% to about 50% by weight of the first part of the composition; and iii) Adhesion accelerators; and b) The second part of the primer composition contains: i) A nitrogen-containing compound present in an amount of about 0.05% by weight to about 10% by weight of the second part of the composition; ii) a copper-based catalyst present in an amount of about 0.1% to about 15% by weight of the second part of the composition; and iii) Diluent components; The composition provides a room temperature fixation time of about 5 to about 35 seconds; and After curing at room temperature on a substrate for 24 hours, the composition has a shear strength of about 2.5 MPa to about 10 MPa.

[0014] Another advantageous aspect of the invention provides a primer composition miscible with hydrocarbon oils, comprising: i) Amine activator compounds; ii) Copper-based catalysts; and iii) One or more diluents comprising a (meth)acrylate hydroxyalkyl ester monomer and a solvent; The percentage ratio of the (meth)acrylate hydroxyalkyl ester monomer, the solvent, and the copper-based catalyst is about 65 to about 80, about 15 to about 30, and about 0.5 to about 15 by weight of the second part of the composition. Detailed Implementation

[0015] definition The terms “hydrocarbon oil,” “cutting oil,” and “stamping oil” as used herein refer to fluids used, particularly for cooling, lubrication, rust prevention, or chip flushing in mechanical metal cutting operations, or for other special effects in other metal processing operations, and they are used interchangeably.

[0016] The terms “C5-coated substrate,” “C5 electrical steel,” and “CS / EC-5 electrical steel” as used herein refer to a type of low surface energy steel coating and are used interchangeably. CS / EC-5 electrical steel may offer certain advantages, such as increased insulation properties, annealing resistance, and improved weldability. These terms are used interchangeably.

[0017] As used herein, the term "setting time" refers to the time elapsed after an adhesive composition has been applied to a substrate and has reached a certain tensile strength at room temperature. Setting time is a time quantity in which the adhesive-bonded product can withstand a certain amount of movement and / or weight without compromising the bond and therefore the quality of the product, and reaches a certain tensile strength at room temperature after application to the substrate. Setting may be achievable as complete curing, or it may not be; it may be partial curing. Therefore, adhesive compositions need to have rapid setting times to maximize the output of high-quality products and minimize the amount of unusable products, as well as to maximize the speed and efficiency of the assembly process.

[0018] (Meth)acrylate hydroxyalkyl ester monomer The first part of the two-part adhesive composition contains one or more (meth)acrylate hydroxyalkyl ester monomers.

[0019] Among the available hydroxyalkyl methacrylate monomers of the present invention are hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate phosphate (Harcryl 1228), hydroxyethyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, hydroxyethylcaprolactone (meth)acrylate (“HECLA”), hydroxybutyl methacrylate, and combinations thereof.

[0020] In one advantageous aspect of the invention, one or more (meth)acrylate hydroxyalkyl ester monomers may be present in the invention in amounts of about 5% to about 50%, about 10% to about 40%, about 15% to about 30%, or about 20% to about 25%, wherein all amounts are based on the first part composition by weight.

[0021] Multifunctional polyurethane (meth)acrylate oligomers The first part of the adhesive composition of the present invention comprises a multifunctional polyurethane (meth)acrylate oligomer.

[0022] In one advantageous aspect of the invention, the multifunctional polyurethane (meth)acrylate oligomer can have a weight-average molecular weight of about 300 MW to about 16,000 MW. For example, the multifunctional polyurethane (meth)acrylate oligomer can have a weight-average molecular weight of about 300 MW up to any of the following, with the following as the upper limit: about 15,000 MW, about 14,000 MW, about 13,000 MW, about 12,000 MW, about 11,000 MW, about 10,000 MW, about 9,000 MW, about 8,000 MW, about 7,000 MW, about 6,000 MW, about 5,000 MW, about 4,000 MW, and about 3,000 MW. The weight-average molecular weight can be determined using a method consistent with that described in ASTM D5296.

[0023] Among the available multifunctional polyurethane (meth)acrylate oligomers of the present invention are various difunctional aromatic and / or aliphatic polyether urethane acrylate oligomers. Examples of those commercially available substances include BOMAR BR-302 and BR-3747AE, each from Dymax Corporation, Torrington, CT. Other available oligomers include: trifunctional aromatic polyether urethane methacrylate oligomer (BR-1160, Dymax), 2-hydroxy-3-phenoxypropyl methacrylate (SR191B, from the Sartomer division of Arkema Inc.), aromatic hexafunctional urethane acrylate (CN975), aromatic polyether urethane triacrylate oligomer (CN971A80), aliphatic urethane acrylate oligomer (CN9010), and combinations thereof.

[0024] Adhesion promoter The first part of the adhesive composition of the present invention comprises an adhesion promoter.

[0025] Among the available adhesive promoters of the present invention are organic carboxylic acids, including: glacial acrylic acid, methacryloyloxyethyl maleate, maleic acid, methacrylic acid, hydroxyl functional copolymers having acidic groups (e.g., BYK-4510, from Evonik's BYK division), hydroxyethyl methacrylate phosphate, and combinations thereof.

[0026] In one advantageous aspect of the invention, the adhesion promoter may be present in the invention in amounts of about 1.5% to about 12%, about 2.0% to about 8%, about 2% to about 5%, wherein all amounts are based on the first part composition by weight.

[0027] Poly(meth)acrylate crosslinking agent The first part of the adhesive composition of the present invention may further comprise at least one poly(meth)acrylate crosslinking agent.

[0028] Among the one or more poly(meth)acrylate crosslinking agents available in this invention are ethoxylated bisphenol A di(meth)acrylate, tricyclodecanediethanol diacrylate (“TCDDMDA”), SR 368 (tris(2-hydroxyethyl)isocyanurate triacrylate), ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate (SR 295), trimethylolpropane triacrylate (“TMPTA”), trimethylolpropane trimethacrylate (“TMPTMA”), pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, ethoxylated dipentaerythritol pentaacrylate, dipentrairythritol pentaacrylate esters, octahydro-4,7-bridged methylene-1H-indendiylbis(methylene)diacrylate), and combinations thereof.

[0029] In one advantageous aspect of the invention, one or more poly(meth)acrylate crosslinking agents may be present in the invention in amounts of about 5% to about 35%, about 10% to about 35%, about 15% to about 35%, about 20% to about 35%, about 25% to about 35%, or about 30% to about 35%, wherein all amounts are based on the first part composition by weight.

[0030] (Meth)acrylate monomers The first part of the adhesive composition of the present invention may further contain at least one (meth)acrylate monomer.

[0031] Among the available (meth)acrylate monomers of the present invention are 3,3,5-trimethylcyclohexyl methacrylate (“TMCHMA”), methyl methacrylate (“MMA”), diethylene glycol methyl ether methacrylate (SR545), isobornyl acrylate (“IBOA”), isobornyl methacrylate (“IBOMA”), trimethylcyclohexyl methacrylate (SR421A), tricyclodecanediethanol diacrylate (SR833S), tetrahydrofurfuryl methacrylate, tetrahydrofurfuryl methacrylate, ethyl methacrylate, 2-ethylhexyl acrylate, 2-hydroxy-3-phenoxypropyl methacrylate, benzyl methacrylate, 4-(1,1-dimethylethyl)cyclohexyl acrylate (“TBCHA”), and combinations thereof.

[0032] In one advantageous aspect of the invention, the (meth)acrylate monomer may be present in the invention in an amount of about 5% to about 15%, preferably about 6% to about 12%, wherein all amounts are by weight of the first part of the composition.

[0033] Nitrogen compounds The second part of the primer composition of the present invention comprises nitrogen-containing compounds.

[0034] Among the nitrogen-containing compounds available in this invention are tributylamine (98%), triethylamine, N,N-diethanol-p-toluidine, 3,5-diethyl-1-phenyl-2-propyl-1,2-dihydropyridine (“PDHP”), and N,N-dimethylaniline. Additionally, saccharin, toluidine (e.g., N,N-diethyl-p-toluidine and N,N-dimethyl-o-toluidine), and acetylphenylhydrazine (“APH”) may be used.

[0035] In one advantageous aspect of the invention, the nitrogen-containing compound may be present in the invention in amounts of about 0.05% to about 10%, about 0.5% to about 7%, or about 2% to about 5%, wherein all amounts are based on the second part composition by weight.

[0036] Copper-based catalysts The second part of the primer composition of the present invention comprises a copper-based catalyst.

[0037] Among the copper-based catalysts available in this invention are copper carbonate, copper(II) acetylacetonate, copper acetate, copper sulfate, copper carbonate hydroxide, copper glycinate, copper benzoate, copper gluconate, and combinations thereof.

[0038] In one advantageous aspect of the invention, the copper-based catalyst may be present in the invention in amounts of about 0.1% to about 15%, about 1% to about 10%, or about 2% to about 8%, wherein all amounts are based on the second part composition by weight.

[0039] diluent components The second part of the primer composition of the present invention comprises a diluent component.

[0040] In one advantageous aspect of the invention, the diluent component comprises a solvent, a (meth)acrylate monomer, and combinations thereof.

[0041] In another advantageous aspect of the invention, when hydrocarbon oil is present, the diluent component preferably comprises both a solvent and a (meth)acrylate monomer. The presence of both the solvent and the (meth)acrylate monomer provides a primer that is soluble in cutting oil and maintains high strength and rapid setting. Cutting is used in some mechanical metal cutting operations. Therefore, a primer that is soluble in cutting oil allows the primer to properly contact and spread on the surface where the cutting oil is present to provide a uniform amount of primer. A primer miscible with cutting oil also allows the metal cutting operation to simultaneously apply the primer and the cutting oil.

[0042] Among the solvents available in this invention are acetone, ethoxylated alcohols, ethoxylated oleyl alcohol (Chemonic OE10), isopropanol, 2-ethylhexanoic acid, toluene, heptane, chloroform, methanol, ethyl acetate, ethylene glycol, dimethyl sulfoxide, trichloroethylene, isopropanol, decafluoropentane, n-butanol, and combinations thereof.

[0043] In one advantageous aspect of the invention, the solvent may be present in amounts of about 75% to about 99%, about 80% to about 99%, about 85% to about 99%, about 90% to about 99%, or about 95% to about 99%, wherein all amounts are based on the second part of the composition by weight.

[0044] Among the available (meth)acrylate monomers that can be used as part of the diluent (in Part II) may be hydroxypropyl methacrylate, hydroxyethyl methacrylate, ethoxylated bisphenol A dimethacrylate, 3,3,5-trimethylcyclohexyl methacrylate (“TMCHMA”), methyl methacrylate (“MMA”), diethylene glycol methyl ether methacrylate (SR 545), isobornyl acrylate (“IBOA”), isobornyl methacrylate (“IBOMA”), trimethylcyclohexyl methacrylate (SR 421A), tricyclodecanediethanol diacrylate (SR 833S), 2-hydroxy-3-phenoxypropyl methacrylate, tricyclodecanediethanol diacrylate (“TCDDMDA”), octahydro-4,7-bridged methylene-1H-indendiyl bis(methylene) diacrylate, pentaerythritol tetraacrylate, and combinations thereof.

[0045] In one advantageous aspect of the invention, the (meth)acrylate monomer may be present in the diluent component of the second part in an amount of about 85% to about 99%, preferably about 90% to about 99%, for example about 95% to about 99%, wherein all amounts are based on the composition of the second part by weight.

[0046] In another advantageous aspect of the invention, the diluent component comprises both a solvent and a (meth)acrylate monomer. In this aspect, the solvent may be present in an amount of about 15% to about 30% by weight of the second part of the composition, and the (meth)acrylate monomer may be present in an amount of about 65% to about 80% by weight of the second part of the composition.

[0047] In another advantageous aspect of the invention, the percentage ratio of (meth)acrylate monomer (MM): solvent (Sol): copper-based catalyst (CuCat) in the diluent component of the second part can preferably be about 65 to about 80 (MM): about 15 to about 30 (Sol): about 0.5 to about 15 (CuCat) by weight of the second part composition.

[0048] In another advantageous aspect of the invention, the percentage ratio of (meth)acrylate monomer (MM): solvent (Sol): copper-based catalyst (CuCat) may be 70 to 75 (MM): 22 to 25 (Sol): 0.5 to 15 (CuCat) by weight of the second part of the composition.

[0049] In another advantageous aspect of the invention, the additional (meth)acrylate monomers of the first part of the composition and the (meth)acrylate monomers of the diluent component of the second part of the composition may be the same or different.

[0050] Accelerator The second part of the adhesive composition of the present invention may further include an accelerator.

[0051] Among the available accelerators of the present invention are GP-APH, amines, peroxides (e.g., tert-butyl peroxybenzoate (Trigonox C)), and combinations thereof.

[0052] In one advantageous aspect of the invention, the accelerator may be present in amounts of about 0.5% to about 5%, about 1% to about 5%, about 2% to about 5%, about 3% to about 5%, or about 4% to about 5%, wherein all amounts are based on the second part composition by weight.

[0053] Other components and / or additives The two-part composition of the present invention may further contain additional components and / or additives.

[0054] In one advantageous aspect of the invention, the stabilizer may be present in amounts of about 0.1% to about 5%, about 0.5% to about 5%, about 1% to about 5%, about 2% to about 5%, about 3% to about 5%, or about 4% to about 5%, wherein all amounts are based on the second part of the composition by weight.

[0055] The compositions of the present invention may contain optional additives, such as, but not limited to, stabilizers, fillers, defoamers, pigments, colorants, plasticizers, viscosity modifiers, toughening agents, coupling agents, adhesion promoters, humectants, tackifiers, flame retardants, wetting agents, thixotropic and / or rheology modifiers, corrosion inhibitors, fluorescent additives, antioxidants, and combinations thereof.

[0056] physical properties The compositions of the present invention can typically have a viscosity of about 80 cPs to about 900 cPs, about 200 cPs to about 800 cPs, about 400 cPs to about 600 cPs, or about 500 cPs to about 600 cPs.

[0057] In one advantageous aspect of the invention, the second portion of the primer composition is miscible with hydrocarbon oil.

[0058] In another advantageous aspect of the invention, the second portion of the primer composition is prepared as a 50 / 50 mixture with the hydrocarbon oil. As previously mentioned, because cutting is used in some mechanical metal cutting operations, a primer that is miscible with the cutting oil allows the primer to properly contact and spread on the surface where the cutting oil is present to provide a uniform amount of primer. The miscibility of the primer with the cutting oil also allows the metal cutting operation to simultaneously apply the primer and the cutting oil.

[0059] In another advantageous aspect of the invention, the primer composition is prepared as a 50 / 50 mixture with a hydrocarbon oil, wherein the percentage ratio of (meth)acrylate monomer (MM): solvent (Sol): copper-based catalyst (CuCat) is about 50 to about 80 (MM): about 15 to about 50 (Sol): about 3 to about 15 (CuCat), wherein all amounts are based on the second part of the composition by weight.

[0060] In one advantageous aspect of the invention, the two-part composition is fixed at room temperature.

[0061] In one advantageous aspect of the invention, the two-part composition is fixed at room temperature for about 5 to 40 seconds, 10 to 40 seconds, 15 to 40 seconds, 20 to 40 seconds, 25 to 40 seconds, 30 to 40 seconds, or 35 to 40 seconds.

[0062] In one advantageous aspect of the invention, the two-part composition is fixed at room temperature on both C5-coated and non-C5-coated substrates for about 5 to 35 seconds, 10 to 35 seconds, 15 to 35 seconds, 20 to 35 seconds, 25 to 35 seconds, or 30 to 35 seconds.

[0063] In one advantageous aspect of the invention, the two-part composition exhibits shear strengths of about 2 MPa to about 15 MPa, about 2.5 to about 10 MPa, or about 6 MPa to about 15 MPa.

[0064] In one advantageous aspect of the invention, the two-part composition preferably exhibits a shear strength of about 2.5 MPa to about 10 MPa when applied to a C5-coated substrate or a non-C5-coated substrate.

[0065] In one advantageous aspect of the invention, the articles can be assembled from the compositions of the invention. The articles can be selected from any number of articles in which room temperature fixed time and high tensile strength are useful. For example, the compositions can be particularly used in the manufacture of, for example, laminated articles, laminated stacks, or rotor assemblies.

[0066] In yet another advantageous aspect of the invention, the article can be assembled from the composition of the invention and may include the following components: a) A first substrate surface having the first portion composition; b) A second substrate surface, optionally having the first portion of the composition; and c) At least one of the first substrate surface or the second substrate surface, having a second portion of the composition covering the first portion of the composition; A first substrate having a first part composition and a second part composition are joined together to form a laminated article.

[0067] In another aspect of the invention, the article can be assembled by repeating the stacking of components a) to c) described above.

[0068] In another advantageous aspect of the invention, the compositions of the invention can be used in a manufacturing method that may include the following steps: a) Depositing a layer of the second part composition onto the surface of the first substrate; b) Depositing a layer of the first portion of the composition onto the surface of the second substrate; and c) A first substrate having the first portion composition and a second portion composition are combined to form a laminated article.

[0069] In another advantageous aspect of the invention, steps a) to c) described above can be repeated to form a laminated stack.

[0070] In one advantageous aspect of the invention, the use of both the first part of the adhesive composition and the second part of the primer composition can promote faster setting time and higher tensile strength.

[0071] In another advantageous aspect of the invention, the compositions of the invention can be used in a manufacturing method that may include the following steps: a) Depositing a layer of the second part composition onto the surface of the first substrate; b) Deposit a layer of the second part of the composition on the surface of the second substrate; c) Depositing the first portion composition onto at least one of a first substrate surface or a second substrate surface having a second portion composition layer; and d) A first substrate having the first portion composition and a second portion composition are combined to form a laminated article.

[0072] In another advantageous aspect of the invention, steps a) to d) described above can be repeated to form a laminated stack.

[0073] In one advantageous aspect of the invention, step c described above (depositing the first portion of the composition onto at least one of the surfaces of a first substrate or a second substrate having a second portion of the composition layer) can promote even faster setting times and higher tensile strength.

[0074] In one advantageous aspect of the invention, the first substrate surface and / or the second substrate surface may include various metal substrate surfaces, which may include, but are not limited to, CS / EC-5 electrical steel, galvanized steel, low carbon steel, stainless steel, other low surface energy substrates, coated metals, and combinations thereof.

[0075] The surfaces of the first substrate and / or the second substrate may be the same or different, and at least one of them is preferably a CS / EC-5 electrical steel substrate.

[0076] In one advantageous aspect of the invention, an article of articles (desired rotor assembly) may be formed using the compositions of the invention, which may include: a laminated stack formed as described herein; a first end cap and a second end cap bonded to the laminated stack using a first portion of the composition; and a shaft bonded to a hole defined by the laminated stack using a first portion of the composition.

[0077] Example Test methods Examples 1 to 5 and Comparative Examples 1 to 7 were evaluated according to the test conditions described below in this document.

[0078] fixed time Tensile lap shear is tested according to ASTM D882-02. A test substrate is used with a nominal length of not less than 4 in., a nominal width of 1 inch, and a thickness of not more than 0.1 in. The substrate is wiped with solvent to remove dirt. The disclosed adhesive composition is applied as part of the substrate surface as an adhesive, and then covered with a second substrate surface on which a primer composition is applied to create a 0.5-inch bonded area without induced gap. The bonded area is then allowed to cure at room temperature for a period of 10 to 80 seconds. The lap shear specimens are tested with different weights at different times to determine their strength; these weights include 61 g, 355 g, and 3 kg. This test determines whether the bond can withstand a specified weight after a specified amount of time. The curing time provided for each composition is the average of the results of 3 to 5 lap shear specimens.

[0079] Tensile lap shear strength Tensile lap shear was tested according to ASTM D882-02. A test substrate was used with a nominal length of not less than 4 in., a nominal width of 1 in., and a thickness of not more than 0.1 in. The substrate was cleaned with isopropyl alcohol to remove dirt and oil. The disclosed adhesive composition was applied as an adhesive to part of the substrate surface, and then covered with a second substrate surface on which a primer composition was applied to create a 0.5-inch bonded area without induced gaps. The bonded area was then allowed to cure at room temperature for approximately 24 hours. The tensile strength under maximum load was recorded. The strength provided by each composition is the average of the results from 3 to 10 lap shear specimens.

[0080] Example 1 – Invention Samples 1 to 5 Weigh all raw materials by mass (g) and mix them in a speed mixer.

[0081] The chemical compositions of Invention Samples 1 to 5 are shown in Table 1 below. Unless otherwise stated, materials are shown in weight percent. Invention Samples 1 to 5 were assigned to Rembrantin EB 5308 C5 electrical steel substrates. For this purpose, these substrates were used in all subsequent evaluations described herein.

[0082] Table 1

[0083] Mechanical properties were tested on the combinations of the two adhesive compositions of samples 1 to 3 with the inventive primer formulation of the second primer sample 4, and compared with combinations of commercially available adhesives (Loctite 648, formulations outside the scope specified in this invention). The results are illustrated in Table 2 below.

[0084] Table 2

[0085] Table 2 shows that when the inventive primer formulation (part 2 primer sample 4) is used in combination with the inventive adhesive formulation (part 1) of samples 1 to 3, higher tensile strength is achieved compared with the combination of the inventive primer formulation (part 2 primer sample 4) and the commercially available adhesive formulation (Loctite 648).

[0086] Mechanical properties were also tested on combinations of the adhesive compositions of Invention Samples 1 to 3 with a 50 / 50 mixture of the Invention Primer Formulation and Cutting Oil (hereinafter referred to as Part 2 Primer Sample 5), and these were compared with combinations of Part 2 Primer Sample 5 with a commercially available adhesive formulation (Loctite 648). The results are illustrated in Table 3 below.

[0087] Table 3

[0088] Table 3 shows that when the inventive primer formulation sample 5 is used in combination with the inventive adhesive formulations of samples 1 to 3, a tensile strength of at least 4.04 MPa is achieved within 15 seconds. In contrast, when the inventive primer formulation of sample 5 is used in combination with a commercially available adhesive formulation (Loctite 648), it does not achieve a fixed time of 15 seconds.

[0089] Comparative Example 1 Mechanical properties were tested on commercially available adhesive compositions (Loctite 648) outside the scope of the invention and commercially available primer formulations (i.e., (Loctite SF 7649) and (Loctite SF 7090)) outside the scope of the invention. The observed results are shown in Tables 4 and 5 below.

[0090] Table 4

[0091] Table 4 illustrates that commercially available two-part compositions falling outside the requirements of this invention do not meet both the required curing time and tensile strength requirements. Although Table 4 shows a tensile strength of 2.86 MPa, the curing time of the adhesive composition of Comparative Example 1 combined with Loctite 7649 when applied to a C5-coated steel substrate is much longer than 35 seconds (80 seconds). Furthermore, Table 4 illustrates that when applied to a C5-coated steel substrate, a curing time of 40 seconds (greater than 35 seconds) results in a tensile strength of only 2.15 MPa.

[0092] Table 5

[0093] Table 5 shows that the setting time for the adhesive composition of Comparative Sample 1 was 20 to 25 seconds. However, the table also records that when applied to a non-C5 electrical steel substrate, the observed tensile strength was only 1.768 to 2.44 MPa.

[0094] Comparative Example 2 Mechanical properties were tested on commercially available adhesive compositions (Loctite 3510) and commercially available primer formulations (Loctite SF 7649) and (Loctite SF 7090). The observed results are recorded in Tables 6 and 7 below.

[0095] Table 6

[0096] Table 6 provides comparative samples using commercially available compositions. These samples failed to provide the rapid setting time and excellent tensile strength observed in this invention. More specifically, Table 6 shows that Comparative Sample 2, when used in combination with Loctite 7649, achieved setting times of 40 and 50 seconds after application to one or more C5-coated steel substrates.

[0097] Table 7

[0098] Table 7 shows that tensile strengths ranging from only 1.804 to 6.62 MPa were achieved. However, when applied to a non-C5 coated steel substrate, the adhesive composition of Comparative Sample 2 achieved a setting time of 35 seconds.

[0099] Comparative examples 3 to 5 The chemical compositions of the samples of Comparative Examples 3 to 5 are shown in Table 8 below, where each quantity is given as a weight percentage.

[0100] Table 8

[0101] * Ethylenediaminetetraacetic acid (EDTA) Mechanical properties were tested on the combination of the comparative adhesive composition and the primer formulation of Part II of the invention from Comparative Sample 4. The observed results are shown in Table 9 below.

[0102] Table 9

[0103] The data recorded in Table 9 show that the tensile strength is weaker when applied to one or more C5-coated steel substrates compared to the data recorded in Table 2 (which gives the combination of the adhesive formulation of Part 1 and the primer formulation of Part 2).

[0104] Comparative sample 5 does not contain hydroxyalkyl (meth)acrylate monomers, while comparative samples 3 and 4 contain more than the optimal amount of hydroxyalkyl (meth)acrylate monomers. Furthermore, comparative samples 3 and 4 do not contain polyurethane (meth)acrylate oligomers, while comparative sample 5 contains more than the optimal amount of polyurethane (meth)acrylate oligomers.

[0105] Comparative Examples 6 and 7 The chemical compositions of the samples of Comparative Examples 6 and 7 are shown in Table 10 below, where each quantity is given as a weight percentage.

[0106] Table 10

[0107] The mechanical properties described above were tested in combination with the comparative adhesive composition and a commercially available primer formulation (Loctite SF 7649). The results are illustrated in Table 11 below.

[0108] Table 11

[0109] Table 11 illustrates that when "epoxy" oligomers are introduced into adhesive formulations, the tensile strength is unacceptable when applied to C5 electrical steel substrates.

Claims

1. A two-part room-temperature curable composition comprising: a) A first-part adhesive composition comprising: i) One or more (meth)acrylate hydroxyalkyl ester monomers present in an amount of about 10% to about 45% by weight of the first part of the composition; ii) a multifunctional polyurethane (meth)acrylate oligomer present in an amount of about 10% to about 50% by weight of the first part of the composition; and iii) Adhesion accelerators; and b) The second part of the primer composition contains: i) A nitrogen-containing compound present in an amount of about 0.05% by weight to about 10% by weight of the second part of the composition; ii) a copper-based catalyst present in an amount of about 0.1% to about 15% by weight of the second part of the composition; and iii) Diluent components; The composition provides a room temperature fixation time of about 5 to about 35 seconds; and After curing at room temperature on a substrate for 24 hours, the composition has a shear strength of about 2.5 MPa to about 10 MPa.

2. The two-part room-temperature curable composition according to claim 1, wherein the nitrogen-containing compound is selected from tributylamine (98%), triethylamine, N,N-diethanol-p-toluidine, 3,5-diethyl-1-phenyl-2-propyl-1,2-dihydropyridine (PDHP), N,N-dimethylaniline, and combinations thereof.

3. The two-part room-temperature curable composition according to claim 1, wherein the second part of the composition is miscible with hydrocarbon oil.

4. The two-part room-temperature curable composition according to claim 1, wherein the hydroxyalkyl methacrylate monomer is selected from hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate phosphate, hydroxyethyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, hydroxyethylcaprolactone (meth)acrylate, hydroxybutyl methacrylate, and combinations thereof.

5. The two-part room-temperature curable composition according to claim 1, wherein the multifunctional polyurethane (meth)acrylate oligomer is selected from difunctional aromatic or aliphatic polyether urethane acrylate oligomers, trifunctional aromatic polyether urethane methacrylate oligomers, 2-hydroxy-3-phenoxypropyl methacrylate, aromatic hexafunctional urethane acrylate, aromatic polyether urethane triacrylate oligomers, aliphatic urethane acrylate oligomers, and combinations thereof.

6. The two-part room-temperature curable composition according to claim 1, wherein the adhesion promoter is an organic carboxylic acid selected from: icy acrylic acid, methacryloyloxyethyl maleate, maleic acid, methacrylic acid, hydroxyl-functionalized copolymers having acidic groups, hydroxyethyl methacrylate phosphate, and combinations thereof.

7. The two-part room-temperature curable composition according to claim 1, wherein the diluent is a (meth)acrylate monomer selected from the following: hydroxypropyl methacrylate, hydroxyethyl methacrylate, ethoxylated bisphenol A dimethacrylate, 3,3,5-trimethylcyclohexyl methacrylate, methyl methacrylate, diethylene glycol methyl ether methacrylate, isobornyl acrylate, isobornyl methacrylate, trimethylcyclohexyl methacrylate, tricyclodecanediethanol diacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, tricyclodecanediethanol diacrylate, octahydro-4,7-bridged methylene-1H-indendiylbis(methylene)diacrylate, pentaerythritol tetraacrylate, and combinations thereof, wherein the (meth)acrylate monomer is present in an amount of about 90% by weight to about 99% by weight of the second part of the composition.

8. The two-part room-temperature curable composition of claim 1, wherein the diluent is selected from solvents, (meth)acrylate monomers, and combinations thereof, wherein the solvent is present in an amount of about 15% to about 30% by weight of the second part of the composition, and wherein the (meth)acrylate monomer is present in an amount of about 65% to about 80% by weight of the second part of the composition.

9. The two-part room-temperature curable composition of claim 1, wherein the adhesion promoter is present in an amount of about 1.5% to about 12% by weight of the first part of the composition.

10. A method of manufacturing a laminated article using a two-part room-temperature curable composition according to claim 1, comprising: a) Depositing a layer of the second part composition onto the surface of the first substrate; b) Deposit a layer of the first part of the composition onto the surface of the second substrate; c) A first substrate having the first portion composition and a second portion composition are combined to form a laminated article.

11. A method of manufacturing a laminated article using a two-part room-temperature curable composition according to claim 1, comprising: a) Depositing a layer of the second part composition onto the surface of the first substrate; b) Deposit a layer of the second part of the composition on the surface of the second substrate; c) Depositing the first portion composition onto at least one of the surfaces of a first substrate or a second substrate having a second portion composition layer; d) A first substrate having the first portion composition and a second portion composition are combined to form a laminated article.

12. The method of claim 11, wherein portions a) through c) are repeated to form a laminated stack.

13. A rotor assembly for an electric motor, comprising: Two or more substrates are bonded together by an adhesive composition to form a laminated stack, said adhesive composition comprising: a. A first-part adhesive composition comprising: i) One or more (meth)acrylate hydroxyalkyl ester monomers present in an amount of about 10% to about 45% by weight of the first part of the composition; ii) a multifunctional polyurethane (meth)acrylate oligomer present in an amount of about 10% to about 50% by weight of the first part of the composition; and iii) Adhesion accelerators; and b. The second primer composition, comprising: i) A nitrogen-containing compound present in an amount of about 0.05% by weight to about 10% by weight of the second part of the composition; ii) a copper-based catalyst present in an amount of about 0.1% to about 15% by weight of the second part of the composition; and iii) Diluent components; The composition provides a room temperature fixation time of about 5 to about 35 seconds; and After curing at room temperature on a substrate for 24 hours, the composition exhibits a shear strength of approximately 2.5 MPa to approximately 10 MPa; and c. Using the first portion of the composition, bond the shaft to the hole defined by the laminate stack.